Estudio para la determinación de la vida útil del relleno sanitario del GAD municipal del cantón Salcedo, período 2022. - Vaca Arias, Luis David (2022)
It is considered the Sanitary Landfill useful life, as the time necessary for this final disposal method to fulfill the purpose its functionality, which will depend, not only on the inhabitants number from city, but further, the waste produced generation rate by citizens daily, and in turn, the criteria used for the design and construction, the same; as well as corresponding factors to the volume into compacted solid waste cubic meters, the cover material volume, the stabilized waste volume and the accumulated volume disposed in the sanitary landfill. The consumerist culture has unleashed a considerable increase in the garbage daily generation, which is composed around 50% organic waste. The main aim this study was to determine the Sanitary Landfill useful life from Salcedo Canton Municipal GAD; the used methodology was non-experimental, without intervention; it had a research exploratory level, with a qualitative approach, and the bibliographic systematization technique and it was applied ordinary observation. The got results were: the total study area diagnosis, which covers a 21.83 hectares area; the population projection for the 2041 year, what was 81536 total inhabitants, with 73382 inhabitants waste collection coverage, and a 0.68 Kg/day/inhabitant PPC (production per capita); for the (2021) base year, on the other hand, there is a 67946 inhabitants population and the PPC is 0.48 Kg/day/inhabitant, reaching 90% MSW (municipal solid waste) collection coverage, what 25% is used, at the same time a 6.05 available hectares area for final disposal; it is taken into account that the cover material is waste compacted volume 25% . It was possible to find, what in the landfill, there is an increase in the 25206 m3/year accumulated volume, equivalent to 6.45%. It is concluded that the landfill under study useful life, based on a 20 year projection, it is 19 years 10 months and 14 days, for a corresponding landfill volumetric capacity to 413000 m3.